2004
DOI: 10.1080/0032472042000272375
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the stability of census-based racial/ethnic classifications: The case of Brazil

Abstract: This study presents a method of estimating the degree to which people change their racial/ethnic identity from one census enumeration to another. The technique is applied to the classification of skin colour in Brazil (white, black, brown, yellow). For the period 1950-80, the findings show a deficit of 38 per cent in the black category and a gain of 34 per cent in the brown category, suggesting that a large proportion of individuals who declared themselves black in 1950 reclassified themselves as brown in 1980… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 15 publications
1
36
0
6
Order By: Relevance
“…This surplus implies that at least 2.2 million people in 2000 were newly reclassified blacks. In relative terms, this represents a net increase of 33% due to racial reclassification alone, which contrasts with the net decrease of 4% experienced by the black category in the 1980s, as documented by Carvalho et al (2004). The estimates for the period between 2000 and 2010 show that the number of newly reclassified blacks continued to grow.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…This surplus implies that at least 2.2 million people in 2000 were newly reclassified blacks. In relative terms, this represents a net increase of 33% due to racial reclassification alone, which contrasts with the net decrease of 4% experienced by the black category in the 1980s, as documented by Carvalho et al (2004). The estimates for the period between 2000 and 2010 show that the number of newly reclassified blacks continued to grow.…”
Section: Resultsmentioning
confidence: 76%
“…11 Since the race question was not asked in the 1970 census, a mean decadal reclassification rate for the 1960s and 1970s was obtained by dividing the estimated rate for the 1960-80 period by two. This is a simplification of the more complex procedure proposed by Carvalho et al (2004) to convert a rate of reclassification to a decadal basis. Nonetheless, separate calculations showed that their more elaborate technique 11 The child survival method and the model life tables presented by Frias and Rodrigues (1980) were used to estimate intercensal survival rates, following the same method described in section 4 for the 1990s and 2000s.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations